Supervisi Akademik Melalui Pelaksanaan Pelatihan Dalam Meningkatkan Kompetensi Pedagogik Guru Di TK Negeri Se-Kabupaten Bireuen: Penelitian - Syarifah Halimah; Najmuddin; Munawar (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The purpose of this study is to determine academic supervision through the implementation of training in improving teacher pedagogical competence in State Kindergartens throughout Bireuen Regency. The approach to this study uses a descriptive qualitative research method. With data collection techniques, namely observation, interviews and documentation. Data analysis techniques use data reduction, data presentation and drawing conclusions/verification. The results of the study indicate that: (1) At the planning stage of academic supervision through the implementation of training in improving teacher pedagogical competence in State Kindergartens throughout Bireuen Regency, it shows that the planning of academic supervision by the principal in improving teacher pedagogical competence can be said to be running well and also what has been planned has produced results and has been achieved optimally. (2) At the stage of implementing academic supervision through the implementation of training in improving teacher pedagogical competence in State Kindergartens throughout Bireuen Regency, it shows that the implementation of supervision is as effective as possible so that it can be a solution to various deficiencies in problems related to educators in general. The principals of State Kindergartens throughout Bireuen Regency can provide understanding and are able to carry out supervision. (3) At the stage of evaluating academic supervision through the implementation of training to improve the pedagogical competence of teachers in State Kindergartens throughout Bireuen Regency, it was shown that the evaluation of academic supervision in State Kindergartens throughout Bireuen Regency was to improve the pedagogical competence of teachers.